(3GdJbQjH hGdJjSjQ aj CUhd GdMOjKs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s ((3ehSi Hf eMeO Hf EHQGgje GdWQGHdSi GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg GdaJGM GdefGf GeG HYO aEf Yde GdMOjK ef CaVd GdbQH Edi QH GdYGdejf GdMOjK UMjM hMSf hVYja s
(3BNQgG (B:s
(3bGd YHO Gddg Hf GdeHGQc hZjQg ef CbGe ai HdO CQHY Sfjf fSH EdjgG hGddg CYde hCfG OeTbi MeGgG Gddg JYGdi hUGfgG hSGFQ HdGO GdeSdejf hGdMeO ddg s
(3GdEQTGO gh eNJUQ Ydhe GdMOjK dCHh YeQh YKeGf Hf YHO GdQMef GdeYQha HGHf GdUdGMs
(3GdfSNI ef JMHjS CHj GdYHGS GdefUhQ HGddg Ydi LGeY GdbQhjjf HaGSs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
Keywords: (3GdMOjK h GdeUWdMs